A Study of Code-Mixing Used in Daniel Mananta's YouTube Podcast Interview with Putri Tanjung (Sastra Inggris UNPAM, 2026)
This research explores the types of code-mixing that appear in the conversation and the reasons for their use, drawing on Hoffman's (1991) theoretical framework. The data were taken from a YouTube podcast episode in which Daniel Mananta interviewed Putri Tanjung, a conversation containing numerous instances of Indonesian mixed with English. This study employed a qualitative descriptive approach to examine utterances exhibiting code-mixing. The results indicate that the podcast features three main types of code-mixing: intra-sentential, intra-lexical, and changes in pronunciation. Among these, intra-sentential code-mixing appears most frequently, characterized by the insertion of English words or phrases within Indonesian sentences. Based on Hoffman's framework, the primary reasons for code-mixing include discussing specific topics, quoting someone else's statement, emphasizing certain points, using interjections, repeating words for clarification, and clarifying messages for the listener. In summary, the use of code-mixing in this podcast serves both communicative and social functions, illustrating how bilingual speakers express identity, demonstrate fluency, and exhibit adaptability in digital conversations. This research contributes to the understanding of how Indonesian speakers naturally blend languages as part of contemporary media communication